Headed Steel Anchor under Combined Loading - McMackin, Patrick J.; Slutter, Roger G.; Fisher, John W. (Engineering Journal, 1973)
The increasing use of headed steel anchor studs under combined shear and tension loading has resulted in a need for more information on their behavior and strength. Some typical situations where this type of loading is encountered in design are shown schematically in Fig. 1. Anchor studs can provide an efficient method of joining steel and concrete members and can permit greater flexibility in the design of composite steel-concrete systems. The existing criteria for designing headed steel anchor studs with partial embedment in concrete is based on limited test data and various models representing connector behavior. Several empirical relationships have been suggested in the literature. However, a number of factors can affect the ultimate strength of a headed steel anchor stud. They include the embedment length, the development of full or partial concrete shear cones which depends on anchor spacing and boundary conditions, concrete shear strength, shear friction, and the attachment plate thickness.